Neuroprotective Potential of Glycyrrhizic Acid in Ischemic Stroke: Mechanisms and Therapeutic Prospects - Yanwen Li; Juan Wu; Fang Du; Tao Tang; Jonathan Chee Woei Lim; Thilakavathy Karuppiah; Jiaxin Liu; Zhong Sun (Pharmaceuticals)
Background/Objectives: Ischemic stroke is a leading cause of disability and mortality worldwide, with current therapies limited in addressing its complex pathophysiological mechanisms, such as inflammation, oxidative stress, apoptosis, and impaired autophagy. Glycyrrhizic acid (GA), a bioactive compound from licorice (Glycyrrhiza glabra L.), has demonstrated neuroprotective properties in preclinical studies. This review consolidates current evidence on GA’s pharmacological mechanisms and assesses its potential as a therapeutic agent for ischemic stroke. Methods: This review examines findings from recent preclinical studies and reviews on GA’s neuroprotective effects, focusing on its modulation of inflammation, oxidative stress, apoptosis, and autophagy. Studies were identified from major scientific databases, including PubMed, Web of Science, and Embase, covering research from January 2000 to August 2024. Results: GA has demonstrated significant neuroprotective effects through the modulation of key pathways, including HMGB1/TLR4/NF-κB and Keap1/Nrf2, thereby reducing neuroinflammation, oxidative stress, and apoptosis. Additionally, GA promotes autophagy and modulates immune responses, suggesting it could serve as an adjunct therapy to enhance the efficacy and safety of existing treatments, such as thrombolysis. Conclusions: Current findings underscore GA’s potential as a multi-targeted neuroprotective agent in ischemic stroke, highlighting its anti-inflammatory, antioxidant, and anti-apoptotic properties. However, while preclinical data are promising, further clinical trials are necessary to validate GA’s therapeutic potential in humans. This review provides a comprehensive overview of GA’s mechanisms of action, proposing directions for future research to explore its role in ischemic stroke management.